Pengaruh Affiliate Marketing, Live Shopping, Price Discount terhadap Impulse Buying Produk Hanasui di E-Commerce Shopee: Studi pada Generasi Z di Surabaya - Riska Nur Khaula; Ety Dwi Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The development of digital technology has driven significant changes in consumer behavior, particularly in online shopping activities. Generation Z, as active e-commerce users, shows a high tendency for impulse buying, especially in purchasing skincare products. The purpose of the research is to analyze whether affiliate marketing, live shopping, and price discounts influence the impulse buying of Hanasui products on Shopee. The method used falls under quantitative research with an associative causal study. The population used in this study consists of followers of the Hanasui Official Shop on Shopee, with a total of 96 respondents. The sampling technique used was non-probability sampling, which falls under purposive sampling. Based on the research results, it is concluded simultaneously that affiliate marketing, live shopping, and price discounts have a significant influence on the impulse buying variable. Partially, affiliate marketing and live shopping have been proven to significantly and positively influence impulse buying, whereas the price discount variable has been shown to have no effect.